Normalistas campinenses: o projeto curricular da escola normal estadual de Campina Grande-PB (1960 - 1971) - Sousa, Pamella Tamires Avelino de (2023)
The creation of the first public Normal School in Campina Grande-PB, in 1960, complied with a Federal Government development policy, which provided that normal schools should be created, restructured and reformulated. This initiative aimed to expand Normal Education and professionalize more female educators for the developing nation. This research intends to analyze the curriculum developed at the Escola Normal Estadual de Campina Grande (ENECG), between 1960-1971, starting in 1960, when this school was created, and, finally, 1971, taking as reference the brazilian law number: 5.692/71, which reformulates the teaching of 1st and 2nd grades. The documental research analyzes, based on the Evidence Paradigm, the sources found in the data collection, and aims – from the Diário da Borborema newspaper, documents and photographs – to analyze the curriculum developed at ENECG, from the perspective of the analysis categories of Representation, Curriculum and Discipline. The composition of sources such as newspaper, photography, official documents and evaluation exams outlined the prevailing school culture in that Institution, allowing us to conclude that the curriculum developed at ENECG, during the period from 1960 to 1971, was based on the ideas of moral and civic responsibility of the normalists to play the role of mother, wife and daughter for Campinense education.